Platelet Biomarkers in Patients with Atherosclerotic Extracranial Carotid Artery Stenosis: A Systematic Review. (March 2022) - Subramanian, Arun; Delaney, Siobhan; Murphy, Stephen J.X.; Smith, Deirdre R.; Offiah, Chika; McMahon, Jean; de Borst, Gert J.; Naylor, A. Ross; Hamilton, George; Kinsella, Justin A.; McCabe, Dominick J.H.
Abstract : Objective: The aim was to enhance understanding of the role of platelet biomarkers in the pathogenesis of vascular events and risk stratifying patients with asymptomatic or symptomatic atherosclerotic carotid stenosis. Data Sources: Systematic review conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Review Methods: A systematic review collated data from 1975 to 2020 on ex vivo platelet activation and platelet function/reactivity in patients with atherosclerotic carotid stenosis. Results: Forty-three studies met the inclusion criteria; the majority included patients on antiplatelet therapy. Five studies showed increased platelet biomarkers in patients with ≥ 30% asymptomatic carotid stenosis (ACS) vs . controls, with one neutral study. Preliminary data from one study suggested that quantification of "coated platelets" in combination with stenosis severity may aid risk stratification in patients with ≥ 50% – 99% ACS. Platelets were excessively activated in patients with ≥ 30% symptomatic carotid stenosis (SCS) vs . controls (≥ 11 positive studies and one neutral study). Antiplatelet-High on Treatment Platelet Reactivity (HTPR), previously called "antiplatelet resistance", was observed in 23% – 57% of patients on aspirin, with clopidogrel-HTPR in 25% – 100% of patients with ≥ 50% – 99% ACS. Aspirin-HTPR was noted in 9.5% – 64% and clopidogrel-HTPR in 0 – 83% of patients with ≥ 50% SCS. However, the data do not currently support the use of ex vivo platelet function/reactivity testing to tailor antiplatelet therapy outside of a research setting. Platelets are excessively activated ( n  = 5), with increased platelet counts ( n  = 3) in recently symptomatic vs . asymptomatic patients, including those without micro-emboli on transcranial Doppler (TCD) monitoring ( n  = 2). Most available studies ( n  = 7) showed that platelets become more reactive or activated following carotid endarterectomy or stenting, either as an acute phase response to intervention or peri-procedural treatment. Conclusion: Platelets are excessively activated in patients with carotid stenosis vs . controls, in recently symptomatic vs . asymptomatic patients, and may become activated/hyper-reactive following carotid interventions despite commonly prescribed antiplatelet regimens. Further prospective multicentre studies are required to determine whether models combining clinical, neurovascular imaging, and platelet biomarker data can facilitate optimised antiplatelet therapy in individual patients with carotid stenosis.